2010
DOI: 10.1007/s00359-010-0534-4
|View full text |Cite
|
Sign up to set email alerts
|

Pheromones in birds: myth or reality?

Abstract: Birds are anosmic or at best microsmatic… This misbelief persisted until very recently and has strongly influenced the outcome of communication studies in birds, with olfaction remaining neglected as compared to acoustic and visual channels. However, there is now clear empirical evidence showing that olfaction is perfectly functional in birds and birds use olfactory information in a variety of ethological contexts. Although the existence of pheromones has never been formally demonstrated in this vertebrate cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 135 publications
0
51
0
Order By: Relevance
“…In comparison, changes in olfaction (i.e. sense of smell) have received limited attention, which may be due, in part, to the preconceived notion that olfaction was a declining sensory modality during bird evolution [18][19][20][21] and to the historical misconception that birds have a poor sense of smell [22]. Birds are now known to have a wide range of olfactory capabilities, which are used for a variety of purposes, such as foraging, orientation and social interactions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, changes in olfaction (i.e. sense of smell) have received limited attention, which may be due, in part, to the preconceived notion that olfaction was a declining sensory modality during bird evolution [18][19][20][21] and to the historical misconception that birds have a poor sense of smell [22]. Birds are now known to have a wide range of olfactory capabilities, which are used for a variety of purposes, such as foraging, orientation and social interactions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been shown that olfaction may be a more important sense in birds than was traditionally believed (Steiger et al 2008). Recent evidence suggests that birds can use odours in several ecological contexts and with different functions (Roper 1999, Hagelin 2007, Hagelin & Jones 2007, Rajchard 2007, 2008, Balthazart & Taziaux 2009, Caro & Balthazart 2010. At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010).…”
mentioning
confidence: 99%
“…Recent evidence suggests that birds can use odours in several ecological contexts and with different functions (Roper 1999, Hagelin 2007, Hagelin & Jones 2007, Rajchard 2007, 2008, Balthazart & Taziaux 2009, Caro & Balthazart 2010. At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010). For example, birds can recognize their nest using chemical cues (Mínguez 1997, O'Dwyer et al 2008, Bonadonna & Bretagnolle 2002, Bonadonna et al 2003a,b, 2004, de León et al 2003, Caspers & Krause 2011 and they are able to discriminate the scent of their partners from the scent of other conspecifics (Bonadonna & Nevitt 2004, Jouventin et al 2007.…”
mentioning
confidence: 99%
“…Identifying cues that influence animal distribution and habitat selection enable decisions to be made on area protection, encouraging population, community and landscape conservation. Although this review addressed mammals a growing body of evidence indicates that birds not only possess but utilise a functional, and in some cases highly developed olfactory system (see Caro and Balthazart, 2010 We also thank three anonymous referees for their constructive feed back in shaping this manuscript.…”
Section: Resultsmentioning
confidence: 99%